Rural cooperatives: An opportunity to rethink the role of the State in the face of seed regulation effects in Colombia (2020)
This paper analyzes the causes that affect the rural sector in Colombia, making farmers vulnerable. The situation is made worse as a result of the seed certification regime that prohibits farmers from replanting non-certified parental material. The authors present some reflections from an analytical-deductive approach, with an invitation to rethink the role of the State, to guarantee their rights. As a result, the cooperativism is proposed as a solution to this problem, through rural cooperatives as a driving force for the recovery and revitalization of the countryside